UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA DINI PADA MATERI MENGENAL BENTUK GEOMETRI MELALUI PENERAPAN MODEL MAKE A MATCH - Widia Nurjanah (Jurnal El-Audi, 2022)
Cognitive ability can be interpreted as the ability to know something, showing the ability to capture the nature, meaning, or information about something and have a clear picture of it. This study aims to analyze an effort to improve the cognitive abilities of early childhood on the subject of recognizing geometric shapes through the application of the make a match model. This research approach is qualitative research. the type of research used is Classroom Action Research (CAR). The subjects in this study were all children aged 5-6 years in Raudhatul Athfal Miftahul Huda Nagrak T.A 2019-2020, totaling 16 children. The results of the study show that the application of the Make A Match learning model can improve the cognitive abilities of early childhood in recognizing geometric shapes at Raudhatul Athfal Miftahul Huda. With the initial percentage before using the Make A Match model 43.75% after using it in Cycle I it became 62.67% and completeness increased in Cycle II to 81.51% from the success indicator of 75%.